P16/Ki-67 Dual Staining Improve Detection of High-Grade Intraepithelial Lesions and Cervical Cancer. - Rasheed, Enas Abd Al Majed; Abdul Ghani, Mohand Mundher; Al-Obaidi, Salim Rasheed (International Journal of Psychosocial Rehabilitation, 2020)
Abstract--Worldwide, cervical intraepithelial lesions are common in adult women , after the age of 30 years . The high grade lesions are precancerous and could transformed to in situ and invasive squamous cell carcinoma of uterian cervix .These transformation significantly can be reduced by screening program of the cervix ,namely : cytology, HR-HPV test , and colposcopy .Women with cytology of utrian cervix that showed morphology of intraepithelial lesions ,especially high grade lesions , HR-HPV test should be done for these women . However , high prevalence of HPV infection can`t predicate the risk of malignant transformation in these women , thus additional triage test , including biomarkers for transformed cells can be used to detect women need further evaluation , follow up and treatment .In current study , p16/Ki-67 dual immunostaining , was used for cytology as biomarker for detection of cellular changes and can improve the diagnosis of precancerous lesions and cervical squamous cells carcinoma .Aim of the study: To identify the role of p16/ki-67 dual immunostaining in predicting the presence of significant cervical lesions in women with mild cytological atypia .Patients , material and method: A prospective study of 317 women , with average age 39 years , over a period of December 2017 to August 2019, in Bagdad city and Salahaden Government .Patients were referred from private gynecological clinics to private lab of Dr.Salim Rasheed Al-Obaidi in Baghgad city and Lab of Dr. Inas Abd Al Majed Rasheed in Salahaden Government. All cytological smears from these women that were showed cytological morphology of intraepithelial lesions , were tested for HR-HPV ( by PCR ) , and p16/ki-67 dual immunostaining of cytology followed by colposcopy-guided biopsy were done for 58 women .Results: Positively staining cells for p16/Ki-67 dual staining showed dark red –red brown nuclei , with clear or brownish cytoplasm . Positive slides are defined by presences of one or more cervical epithelial cells that expressed simultaneously stained for both p16/Ki-67 markers.It has been shown the sensitivity and specificity of immunostaining in diagnosis of CIN2/CIN3 for ASC-US and LSIL lesions were (100 and 73%), and (100-89.7%) respectively.p16/ki-67 immunostaining positivity also increased with cytological severity in corresponded to histological morphology.Conclusion: In addition to cytological evaluation and HR-HPV testing in women with cervical intraepithelial lesions , p16/ki-67 dual immunostaining of useful value in triage of ASC-US and LSIL lesions , according to high sensitivity and specificity .